Does bioelectrochemical cell configuration and anode potential affect biofilm response?. (21st November 2012) - Kumar, Amit; Katuri, Krishna; Lens, Piet; Leech, Dónal
Abstract : Electrochemical gradients are the backbone of basic cellular functions, including chemo-osmotic transport and ATP synthesis. Microbial growth, terminal respiratory proteins and external electron transfer are major pathways competing for electrons. In BESs (bioelectrochemical systems), such as MFCs (microbial fuel cells), the electron flow can be via soluble inorganic/organic molecules or to a solid surface. The flow of electrons towards a solid surface can be via outer-membrane cytochromes or electron-shuttle molecules, mediated by conductive protein nanowires or extracellular matrices. In MECs (microbial electrolysis cells), the anode potential can vary over a wide range, which alters the thermodynamic energy available for bacteria capable of donating electrons to the electrode [termed EAB (electroactive bacteria)]. Thus the anode potential is an important electrochemical parameter determining the growth, electron distribution/transfer and electrical activity of films of these bacteria on electrodes. Different optimal applied potentials to anodes have been suggested in the literature, for selection for microbial growth, diversity and performance in biofilms on electrodes. In the present paper, we review the effects of anode potentials on electron-transfer properties of such biofilms, and report on the effect that electrochemical cell configuration may have on performance.